Peran Pendidik dalam Pengembangan Identitas Diri Mahasiswa melalui Character Building - Fadhillah, Is; Wulan, Tri (Efektor, 2020)
Currently, educators have a big task in their role in the success of the nation's children. One of the fundamental problems currently occurring among students as the next generation is the tendency of moral degradation. This study aims to determine how far the understanding of educators is about social phenomena that occur in student identity, so it is necessary to implement a character-building program in students as an effort to develop student identity, as well as identify what efforts are made by educators in implementing character building in students of the Ganesha Husada College of Health, Kediri Regency. This research uses a qualitative case study method. In this framework, a paradigmatic analysis of social construction theory is used in analyzing the data materials of character building. Data collection was carried out through in-depth interviews. The results obtained, the social construction steps regarding character building in the campus environment of Stikes Ganesha Husada Kediri, among which the most prominent is the curriculum setting. As a capital from exemplary in each lecturer, internalization of character building which becomes a plus icon is quickly understood and practiced by students. Therefore, the implementative values of character building can eventually become a new culture for students of Stikes Ganesha Husada Kediri.